2019
DOI: 10.1128/aac.01394-19
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Candida albicans Biofilm Formation in Clinical Lipid Emulsions Due to Capric Acid-Mediated Inhibition

Abstract: Receipt of parenteral nutrition (PN) remains an independent risk factor for developing catheter-related bloodstream infections (CR-BSI) caused by fungi, including by the polymorphic fungus Candida albicans, which is notoriously adept at forming drug-resistant biofilm structures. Among a variety of macronutrients, PN solutions contain lipid emulsions to supply daily essential fats and are often delivered via central venous catheters (CVCs). Therefore, using an in vitro biofilm model system, we sought to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Murzyn and colleagues ( 63 ) have shown that purified C 10:0 inhibited C. albicans filamentation and reduced its capacity to adhere and form biofilm. Willems and colleagues ( 64 ) have confirmed the inhibitory activities of C 10:0 incorporated in lipid emulsions. Notably, in both studies, C 10:0 did not suppress yeast growth.…”
Section: Discussionmentioning
confidence: 86%
“…Murzyn and colleagues ( 63 ) have shown that purified C 10:0 inhibited C. albicans filamentation and reduced its capacity to adhere and form biofilm. Willems and colleagues ( 64 ) have confirmed the inhibitory activities of C 10:0 incorporated in lipid emulsions. Notably, in both studies, C 10:0 did not suppress yeast growth.…”
Section: Discussionmentioning
confidence: 86%
“…However, our findings are supported by other studies. These studies have proven that C. albicans has a unique sensitivity to medium-chain fatty acids with carbon chain lengths of C8, C10, and C12, represented by caprylic, capric, and lauric acid, respectively 29,30 . The abovementioned medium-chain fatty acids have been demonstrated to have antifungal effects 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Swindell K. pointed out that 10% of lipid emulsion was conducive to the germination of Ca spores and the growth of mycelia (18). The spores and mycelia of Ca could provide a lot of adhesion sites for E. coli, meanwhile, lipid emulsion provided rich nutrients, and promoted the growth of pathogenic bacteria and bio lm formation, which may partly explain why lipid emulsion has a catalytic effect on E. coli-Ca mixed bio lm formation 35 . hDC mainly regulates the biosynthesis of E.coli agellum, bacterial division, and the expression of bacterial virulence genes 36 .…”
Section: Discussionmentioning
confidence: 99%